If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3y + -8) + 2(2y + 10) = 0 Reorder the terms: -4(-8 + 3y) + 2(2y + 10) = 0 (-8 * -4 + 3y * -4) + 2(2y + 10) = 0 (32 + -12y) + 2(2y + 10) = 0 Reorder the terms: 32 + -12y + 2(10 + 2y) = 0 32 + -12y + (10 * 2 + 2y * 2) = 0 32 + -12y + (20 + 4y) = 0 Reorder the terms: 32 + 20 + -12y + 4y = 0 Combine like terms: 32 + 20 = 52 52 + -12y + 4y = 0 Combine like terms: -12y + 4y = -8y 52 + -8y = 0 Solving 52 + -8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + -8y = 0 + -52 Combine like terms: 52 + -52 = 0 0 + -8y = 0 + -52 -8y = 0 + -52 Combine like terms: 0 + -52 = -52 -8y = -52 Divide each side by '-8'. y = 6.5 Simplifying y = 6.5
| -24=-6w+3(w-7) | | 2-3*(x-1)*(x-1)=0 | | (5x/2)-9=0 | | 8*(8b/8) | | 10x^4+28x^3-6x^2=equa | | x=0.625+0.625y+-0.625z | | 9*2-54x=81 | | 25x-12=7x | | x+y=7x-y=5 | | (7-z)(5z+4)=0 | | x+13.9=-7.5 | | X(40+x)=6000 | | -33+53= | | 8x+5z=5+5y | | 7=x(-13+x)-11+6x | | 4x^2-16x=-y^2+10y-40 | | 9x+4x+3+8=4x+3x+8x | | lnx=-1/5 | | 5y-4=13y+68 | | 4x+22=3+7x-8 | | 1/3(x-4)^=1 | | (2000(1-x/60)^2)/x | | 6+1-2x=5x+x-7 | | (5x+20)(3x+66)= | | 6x+7z=4+5y | | Ydy/dx-e^x=O | | 7(2x-9)=43 | | (2s-3)+s+(3s-30)=207 | | r+21=15 | | 5x-3=12+x-1+2 | | 40+2*5= | | k^4-100k=0 |